Persistent Cervical Infection with the Chikungunya Virus - José Eduardo Pérez-Pérez; Oscar Guzmán-Martínez; Jesús Miguel Torres-Flores; Clara Luz Sampieri; Julio Isael Pérez-Carreón; Nayali López-Balderas; Miguel Ángel Barragán; Guillermo Mendoza-Cervantes; Fabio García-García; Alma Campos; David Sánchez-Marín; Hilda Montero (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Chikungunya virus (CHIKV) induces an acute infection known as chikungunya fever; however, the persistence of CHIKV infections has been reported. This report investigated the persistence of CHIKV over six months in the cervix of two infected women. The infectious CHIKV was isolated from three samples. Our findings demonstrated the persistence of CHIKV in the cervix, highlighting the importance of evaluating other tissue types.